APPLICATION OF CHINESE LANGUAGE MODULE FOR IMPROVING LANGUAGE SPEAKING SKILLS - Putu Prinda D’amour Nisa (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2019)
ABSTRACT This research called classroom action research (CAR) which combined with Chinese teaching material products. The researcher tried to use a Chinese module that was made by himself to improve the ability of students' speaking skills by collaborating with the application of the think pair share technique. Pretest Testing, Cycle 1 Test and Cycle 2 Test use the same test questions by testing 30 vocabulary words which is spoken verbally by each student. In the pre-test 21 students (95%) were ranked D and only 1 student (5%) was ranked C. The percentage of each indirect cycle increased until the final result of cycle 2 was 27% of students still ranked D, 50% of students rated C and 23% of students are rated B. This result is quite satisfying for researchers because Mandarin language skills are quite difficult lessons for beginners especially those who have very little study time but are required to master a lot of pronunciation and vocabulary. Keywords: modules, chinese language, think pair share techniques, speaking skills